Social Networks and Social Support in the Success of Creative Startups - Khalil Zaman; Omar Khan; Jamil Khan (Journal of Social Entrepreneurship and Creative Technology, 2024)
The success of creative startups is influenced by various factors, including the role of social networks and social support. As these ventures typically involve innovative ideas and high uncertainty, the social connections entrepreneurs establish can provide essential resources, knowledge, and emotional support. Understanding the impact of these social relationships on startup success is critical for entrepreneurs, investors, and policymakers aiming to foster a conducive environment for growth in creative industries. This study aims to explore the influence of social networks and social support on the success of creative startups. It seeks to identify the types of social support that entrepreneurs rely on, the networks they engage with, and how these factors contribute to their business growth and sustainability. A mixed-methods approach was employed, combining both quantitative and qualitative research methods. Data was collected through surveys of 100 creative entrepreneurs in Indonesia, followed by in-depth interviews with 15 startup founders. The analysis involved statistical techniques to identify patterns in network usage and social support, alongside thematic coding for qualitative insights. The findings reveal that social support, particularly from professional networks and mentorship, is crucial for overcoming challenges in the early stages of startup development. Entrepreneurs with strong connections to industry peers, investors, and mentors reported higher levels of success in securing funding and achieving market growth. Emotional support from family and friends was also found to play a significant role in maintaining resilience and motivation. Social networks and support systems are essential drivers of success for creative startups. Entrepreneurs who actively cultivate these networks tend to navigate challenges more effectively and sustain long-term business growth.